ASSESSMENT OF MATHEMATICS LEARNING BASED ON BANYUMASAN ART CULTURE - Kusno, Kusno; Setyaningsih, Eka; Gunawan, Gunawan; Kusuma, Jaka Wijaya (Tesseract: International Journal of Geometry and Applied Mathematics, 2023)
Learning assessment based on local wisdom is essential in interpreting cultural diversity. This Science and Technology for the Community (IbM) activity aims to socialize ethnomathematics-based mathematics learning assessments, especially Banyumasan art culture. The target of this activity is UMP elementary school teachers in general and UMP elementary mathematics teachers in particular, totaling 22 people. The methods and strategies used in implementing this IbM are starting with a preetest to determine the initial ability of participants, given treatment through book review, discussion, question and answer, simulation and ending with postest and reflection. This activity results in the increasing insight of UMP elementary school teachers on ethnomathematics-based learning assessment, especially Banyumasan art with an average gain of as much as possible. 17.85. The participants' responses to the implementation of this activity were adding insight (59%), valid (19%), welcoming positively and expressing pleasure (22%).